Analysis of the Impact of Electronic Medical Record Implementation on Improving the Effectiveness of Health Service at the West Java Provincial Occupational Health Hospital - Sari, Irda; Saputra, Chandra (International Journal of Psychology and Health Science, 2025)
This study aims to analyze the impact of the implementation of Electronic Medical Records (EMR) on the effectiveness of health services at the West Java Provincial Occupational Health Hospital. The issues raised relate to the effectiveness of the service system, information integration, and the readiness of human resources in facing digital transformation. The method used was a qualitative approach, with data collection techniques through in-depth interviews with health workers, administrative staff, and heads of medical record installations. The results of the study indicate that the implementation of EMR has had a significant impact on improving data access speed, integration between service units, and the accuracy of medical documentation. This system also accelerates administrative processes and clinical actions, reduces the risk of data loss, and strengthens coordination between professions within the hospital environment. However, the implementation of EMR still faces technical challenges such as network disruptions and limitations in supporting infrastructure. From a human resources perspective, adaptation to the new system has been relatively smooth, supported by ongoing training and guidance provided by the hospital. Overall, EMR has proven to be a strategic step toward achieving more efficient, integrated, and data-driven healthcare services in the digital age.